A Welfare Economic Approach to Growth and Distribution in the Dual Economy - Fields, Gary S. (Quarterly Journal of Economics, 1979)
I. Introduction, 325.—II. Absolute and relative approaches for evaluating growth and distribution, 326.—III. A general welfare approach for assessing dualistic development, 328.—IV. Welfare economic analysis of dualistic development: the general case, 334.—V. Welfare economic analysis of dualistic development: special cases, 337.—VI. Extensions of the methodology, 346.—VII. Conclusions and implications, 348.—VIII. Empirical significance, 351.